Non-Cytotoxic Property and DNA Protective Activity against H2O2 and UVC of Thai GAC Fruit Extracts in Human TK6 Cells - Prapaipat Klungsupya, Janram Saenkhum, Thanchanok Muangman, Ubon Rerk-Am, Sarunya Laovitthayanggoon, Wichet Leelamanit (Journal of Applied Pharmaceutical Science)
Momordica cochinchinensis (Lour.) fruit of Cucurbitaceae family is indigenous vegetable and fruit to Southeast Asia. It has been generally known as “GAC” whereas in Thailand it is called “Fhuck-khow”. Regarding its richness in anti-oxidants particularly lycopene and beta-carotene, GAC is named "fruit from heaven" and believed to promote longevity, health and vitality. In present study, GAC extracts were prepared from pulp (PU), skin (SK) and seed membrane (SM) by 50%, 95% ethanol and water (W). MTT assay was done in TK6 cells to determine their cytotoxicity property. The non-cytotoxic extracts were further evaluated for the DNA protective activity against H2O2 and UVC using high alkaline (pH >13) comet assay. TK6 cells (1x105 cells/ml) were pre-incubated with GAC extracts (25, 50 and 100μg/ml) for 24 h prior to an exposure to 50 μM H2O2 and a 254-nm UVC germicidal lamp for DNA damage induction. We found that H2O2-induced DNA damage was suppressed by 30- 60 % when cells were pre-treated with PU, SK and SM extracts at all concentrations used. Regarding test condition used, UVC clearly induced DNA damage in TK6 cells greater that that by H2O2. The protective effect of GAC extracts against UVC was found by 20-30%. Our present results suggest that GAC possesses DNA protective ability against H2O2 and UVC. The degree of anti-oxidative damage activity in TK6 cells of GAC extracts is SK95>SMW>SK50.
Keywords: Momordica cochinchinensis, comet assay, TK6, H2O2, UVC.